Uji Aktivitas Anti Diabetes Ekstrak Umbi Bawang Dayak (Eleutherine Bulbosa) pada Tikus Putih (Rattus Noverginus ) yang Diinduksi Aloksan - Tiara Salsabila; Astriani Natalia Br Ginting; Asyrun Alkhairi Lubis (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
This study aims to examine the antidiabetic activity of ethanol extract of Dayak onion (Eleutherine bulbosa) bulbs in white rats (Rattus norvegicus) induced by alloxan. Diabetes mellitus is a chronic metabolic disease characterized by hyperglycemia due to impaired insulin secretion, insulin resistance, or both. This condition can lead to various serious complications, such as kidney damage, cardiovascular disorders, neuropathy, and impaired wound healing. As the prevalence of diabetes increases globally, the search for safer and more affordable alternative therapies has become a crucial need, especially in developing countries. In recent years, the use of medicinal plants as alternative therapies for diabetes mellitus has received increasing research. Dayak onion is a herbal plant that has long been traditionally used by the people of Kalimantan to treat various diseases, including diabetes. The content of secondary metabolites in Dayak onion bulbs, such as flavonoids, alkaloids, tannins, saponins, and glycosides, is believed to act as a hypoglycemic agent. Flavonoids, for example, are known to have antioxidant activity that can protect pancreatic beta cells from oxidative damage, while saponins can inhibit glucose absorption in the intestine. This study used an experimental method with a post-test only control group design approach. Rats were induced with a certain dose of alloxan to create hyperglycemic conditions, then divided into several groups, including a negative control group, a positive control group (given standard drugs such as metformin), and a treatment group that received ethanol extract of Dayak onion bulbs at varying doses. Blood glucose levels were measured on days 0, 7, and 14 after treatment. It is hoped that the results of this study can provide strong scientific data regarding the potential of Dayak onion extract as an effective and relatively safe antidiabetic agent, as well as become the basis for the development of phytopharmaceutical drugs based on local Indonesian plants.